GHG Emission and Financial Distress: Evidence from Indonesia Listed Firms - Valentine Siagian; Yang-Shin Chen (The Indonesian Journal of Accounting Research, 2026)
This study examines the relationship between greenhouse gas (GHG) emissions and corporate financial distress in an emerging market context. Distinguishing between Scope 1, Scope 2, and Scope 3 emissions, the study investigates whether different categories of carbon exposure exert heterogeneous financial effects. Drawing on stakeholder theory, institutional theory, and the resource-based view, we argue that value-chain emissions (Scope 3) impose greater managerial and financial constraints due to their complexity and limited controllability. Using panel data on Indonesian listed firms over the period 2013–2022, we employ two alternative measures of financial distress and estimate fixed-effects regression models that control for firm characteristics. The results show that Scope 1 and Scope 2 emissions are not significantly associated with financial distress, whereas Scope 3 emissions exhibit a positive and statistically significant relationship. The findings suggest that firms with greater value-chain carbon exposure face higher financial vulnerability, likely due to coordination costs, regulatory pressure, and supply-chain risk. This study contributes to the climate-finance and sustainability accounting literature by demonstrating the importance of disaggregating emissions and highlighting the financial relevance of Scope 3 emissions in emerging markets. The results have implications for managers, investors, and policymakers, emphasizing the need for enhanced supply-chain carbon governance as part of financial risk management.